Workshop on “Advanced laser sensing of gases” – Galileo’s Briefings - , (Il Colle di Galileo, 2018)
A workshop on “Advanced laser sensing of gases” at the CNR-INO headquarters on the Arcetri hill started the new series of seminars called “Galileo’s briefings: Looking beyond”. Three experts in the field were invited to discuss about laser sensing techniques and some of their most exciting applications with researchers from INO and other institutes.